El Sacramentari leccionari de Sant Boi de Lluçanès (Vic, Biblioteca Episcopal, frag. I/5) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2006)
The fragments of the lectionary sacramentary Vic, Bib. Episc., fragment I/5 come from the Sant Boi de Lluçanès parish and allow to reconstruct partially a large manuscript written probably by the Osona canon Recared in the middle of the 10th century. It has thirteen folios containing part of the ordinary, the canon, the Advent texts, the sanctoral of December, Christmas-Epiphany, Lent, the Holy Week, some votive masses, an order «Ad visitandum infirmum» of non-Catalan-Narbonnesse tradition as well as the lectures «In vigilia defunctorum».